Reflection of the Concept of Sanctions and Law on the Tamambaloh Dayak Custom - Efriani Efriani; Edy Agustinus (Kanun Jurnal Ilmu Hukum, 2021)
The phenomenon of sanctions encourages the custom to be labeled “Customary Law” is an interesting phenomenon to be reflected on. In this regard, it reflects on the tradition of the Tamambaloh Dayak ethnicity as social control, and provides a view on the tradition which has the sanctions. This article used an ethnographic qualitative study approach with in-depth observations and interviews. This study described the concept of sanctions on the customs and customary law of the Tamambaloh Dayak in West Kalimantan Province. The results of this study indicated that both customs and customary law in the Tamambaloh Dayak both had sanctions. Sanctions have a function as a symbol of balancing or re-harmonizing the condition of the universe that is experiencing chaos due to human actions. Therefore, sanctions are not interpreted as punishment but as a cultural process.